Geology of the eastern tip of the El Tordell Fault, Southern Pyrenees - Eloi Carola; Josep Anton Muñoz (Journal of Maps, 2024)
Along strike variations of frontal structures at fold and thrust belts allow us deciphering the evolution of contractional structures at early stages of deformation but also, how processes such as salt mobilisation, thrust emplacement, and folding develop. The external parts of the Pyrenees are suitable to investigate how these processes interacted during the Pyrenean Orogeny. The integration of fieldwork and subsurface data allowed us to obtain on the one hand the geological map of the eastern tip of the El Tordell Fault and the Súria Anticline and on the other hand, the 3D structural model of the study area. These two results allowed us to decipher the evolution of the area, which is characterised by the development, under compression, of a salt accumulation at early stages of deformation which was afterwards the locus of the El Tordell Thrust and finally, as deformation progressed, the development of the Súria Anticline.